From Kharijites to IS: Muhammad’s prophecy of extremist thought - Mohamed Ali (2016)
The Prophet Muhammad had prophesied the coming of extremism. The roots of the vicious beliefs of IS can be traced back to the Kharijites - the first extremist group in Islamic history. What were the defining characteristics of the Kharijites and their impact?